Iklim Organisasi Dan Kepuasan Kerja Pegawai Pengadilan Agama Denpasar - Abdul halim Muhammad H.A.Rahman; Nyoman Sri Subawa (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2023)
The Denpasar Religious Court is the only Class I Religious Court in the province of Bali. As a Class I Religious Court, it handles a lot of cases per year, with an insufficient number of employees leading to an increased workload for the staff. Alongside the implementation of the "one day minute and one day publish" program, the Denpasar Religious Court also acts as a coordinator for budget absorption related to DIPA 04, overseeing eight Class II Courts. Furthermore, the less strategic location of the Denpasar Religious Court, due to its off-road placement, makes it challenging for parts of the community to locate the court. The main issue addressed in this study is how the organizational climate and employee job satisfaction at the Denpasar Religious Court are. The objectives of this research are: 1) to examine the organizational climate at the Denpasar Religious Court, and 2) to determine the influence of the organizational climate at the Denpasar Religious Court on employee job satisfaction. The research method utilized in this study is a qualitative approach with thematic analysis. The research findings indicate that: 1) the organizational climate at the Denpasar Religious Court, characterized by supportive leadership, has the strongest influence, along with teamwork and communication; and 2) the organizational climate significantly affects job satisfaction, where motivation, employee commitment, and efficiency are the variables that impact job satisfaction